KAJIAN ETNOSAINS PAUREH SEBAGAI SUMBER PEMBELAJARAN IPA - Melta, Defrian (Pedagogi Hayati, 2024)
Science learning cannot be separated from the environmental context, including local wisdom. One of the treatments known among the people of Padang City is Paureh. Paureh is a concoction consisting of pieces of leaves of medicinal plants which function for the treatment of fever, measles, regurgitation, new homes and so on. The purpose of this research is to analyze and reconstruct the community's knowledge (indigenous science) about Paureh into scientific knowledge in order to find out the types of diseases, traditional medicinal methods and medicinal plants used and it is hoped that it can also contribute information to ethnobotany enthusiasts in developing technology for the utilization of medicinal plants used by various ethnic groups in Indonesia. This study uses an ethnoscience-based qualitative approach with interview and observation methods. Data analysis uses the Miles-Huberman model which includes data reduction, data presentation, drawing conclusions and verification. Based on the results of the study, it showed that the Paureh material had ethnomedicin value that could be used by the community. Reconstruction from community knowledge to scientific knowledge gives scientific meaning to the rules or beliefs that belong to the local community. So that scientific knowledge can be used as a source of learning, especially in science learning.